Sedimentological Observations from the Tiskilwa Till, Illinois, and Sky Pilot Till, Manitoba - Carlson, Anders; Jenson, John; Clark, Peter (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractWe present sedimentological observations from the Tiskilwa Till in northern Illinois, and the Sky Pilot Till in northern Manitoba, that indicate deposition of these tills by subglacial deformation. These generally homogenous tills grade downward into more heterogeneous tills that incorporate underlying sediment into their matrix, indicating entrainment of older sediments by sediment deformation. Deformed sand inclusions within these tills imply deformation of the tills and inclusions prior to deposition. The Tiskilwa Till has relatively high fabric strength throughout its thickness, whereas fabric strength in the Sky Pilot Till generally increases up-section in 2 to 3 m thick increments. Fabric orientations in both tills rotate up-section, possibly due to changes in ice-flow direction associated with the thickening and thinning of ice, and changes in ice-flow divide location. In both the Tiskilwa and Sky Pilot Tills, the change in fabric orientation occurs over intervals of ~1 m, suggesting that the maximum depth of deformation was ≤1 m insofar as any greater depth of deformation would have reoriented till fabric during maximum ice extent and retreat. In the case of the Sky Pilot Till, the up-section increase in macrofabric strength indicates that strain increased up-section. These data suggest that these tills were deposited in a time transgressive manner as strain migrated upwards with the delivery of new till either released from the ice base or advected from up-ice.